Welcome to Software Development on Codidact!
Will you help us build our independent community of developers helping developers? We're small and trying to grow. We welcome questions about all aspects of software development, from design to code to QA and more. Got questions? Got answers? Got code you'd like someone to review? Please join us.
Comments on How to use function composition for applying a function to first elements of a list?
Parent
How to use function composition for applying a function to first elements of a list?
Can anyone explain to me why my Haskell function gives rise to a type-definition error?
Originally, I wrote the following function to subtract one from the first n
elements in a list:
dec_first :: Int -> [Int] -> [Int]
dec_first 0 l = l
dec_first n (x:xs) = (x-1):dec_first (n-1) xs
However, as a challenge, I wanted to write this function using available standard functions, using function compositions. This is how I ended up writing the function (for the subtraction part)
dec_first :: Int -> [Int] -> [Int]
dec_first = map (subtract 1) . take
but this function does not compile due to a type mismatch.
In my attempt to fix the error, I also tried the following variant:
dec_first :: Int -> [Int] -> [Int]
dec_first n = map (subtract 1) . take n
This function actually does work as expected. However, if I specify all parameters again, things breaks again:
dec_first :: Int -> [Int] -> [Int]
dec_first n l = map (subtract 1) . take n l
Can anyone help me understand why this function only works with one variable, but not in the other settings?
Post
The following users marked this post as Works for me:
User | Comment | Date |
---|---|---|
mr Tsjolder |
Thread: Works for me the insight on the signature of the composition operator explains my misunderstanding very well! |
Jul 24, 2023 at 11:53 |
Recall that .
(composition) is defined as:
f . g = \x -> f (g x)
That is, it composes two functions of one argument each. The result (another function of one argument) passes its argument x
to g
, and the result of that to f
.
Your first attempt was:
map (subtract 1) . take
-- inline the definition of (.)
-- with f = map (subtract 1)
-- and g = take
\x -> map (subtract 1) (take x)
This doesn't work because map
expects a list as its second argument, but take x
is not a list. (It is a function mapping lists to lists, [a] -> [a]
.)
Your second attempt:
map (subtract 1) . take n
-- inline the definition of (.)
-- with f = map (subtract 1)
-- and g = take n
\x -> map (subtract 1) (take n x)
This works: take n x
is a list and map
takes a list.
Your third attempt:
map (subtract 1) . take n l
-- inline the definition of (.)
-- with f = map (subtract 1)
-- and g = take n l
\x -> map (subtract 1) (take n l x)
This fails because take n l x
is a type error. It tries to apply take n l
to x
, which would require take n l
to be a function, but it is a list.
In summary, .
composes two functions of a single argument each. map foo . take
fails because take
is a function of two arguments; map foo . take n l
fails because take n l
is not a function at all (it takes zero arguments). In the working version, map foo . take n
, we partially apply take
and take n
is indeed a function of one argument.
In order to compose a function of one argument with a function of two arguments, we could define another operator:
f .: g = \x y -> f (g x y)
Then we could write:
dec_first = map (subtract 1) .: take
Alternatively, we could write:
dec_first = (map (subtract 1) .) . take
-- which is the same as
dec_first = (.) (map (subtract 1)) . take
The reason this works is that the first .
waits for one argument and passes it to take
, then passes the result of that (a partially applied take x
) to another .
, which results in the map (subtract 1) . take x
code that we already know works:
-- inline the first (.)
-- with f = (.) (map (subtract 1))
-- and g = take
dec_first = \x -> (.) (map (subtract 1)) (take x)
-- write (.) in infix notation
dec_first = \x -> map (subtract 1) . take x
We could even write our .:
operator as a composition of compositions:
(.:) = (.) . (.)
-- inline the first layer of (.)
(.:) = \x -> (.) ((.) x)
-- eta-expand
(.:) = \x y -> (.) ((.) x) y
-- convert to infix notation
(.:) = \x y -> ((.) x) . y
-- inline the second layer of (.)
(.:) = \x y z -> (.) x (y z)
-- convert to infix notation
(.:) = \x y z -> x . y z
-- inline the third layer of (.)
(.:) = \x y z w -> x (y z w)
-- rename parameters
(.:) = \f g x y -> f (g x y)
0 comment threads